Cervical spine involvement in pediatric mucopolysaccharidosis patients: Clinical features, early diagnosis, and surgical management - Liu, Hai-Tao; Song, Jia; Zhou, Fu-Chao; Liang, Zhi-Hui; Zhang, Qiu-Qi; Zhang, Yue-Hui; Shao, Jiang (Frontiers in Surgery, 2023)
Abstract Mucopolysaccharidosis (MPS) is a progressive genetic disease that causes a deficiency in lysosomal enzymes, which play an important role in the degradation pathway of glycosaminoglycans. As a result of enzyme defects, mucopolysaccharides cannot be metabolized and thus accumulate. The cervical spine is one of the most commonly involved sites; thus, prompt surgical management before the onset of severe neurological deterioration is critical. However, because of the rarity of the disease, there is no standard treatment. In this review, we characterize the cervical spinal involvement in pediatric patients with MPS, describe the useful imaging technologies for diagnosis, and provide screening procedure for children with MPS. Surgical managements, including indications, surgical methods, possible difficulties, and solutions, are reviewed in detail.